Acceptance and Readiness of Using Smart Phones by Educators to Promote Learning Activity - Devi, K. K. A; Khan, M. M. H. (Peer Review Research Publishing System, 2015)
Mobile technology is providing a new frontier for the application of educational technology within the academia. However, aswith any relatively new technology, much has to be understood about the concept of mobile learning before it can be employedeffectively. One of the most logical early steps is to understand the perception of the stakeholders, including lecturers‟ andstudents. This is the angle of approach taken by INTI International University, Malaysia. This paper presents the results of a surveyat INTI International University, the lecturers about their perception on mobile learning and training. The findings will help in formulating a well-plannedand user-centric approach on application of mobile technology forthe purpose of learning and training within the institution.The results of the survey showed that76.5% of the respondents is owners of smart or mobile phones. The respondents also indicateda favorable perception of m-learning although 64% of them have never used it. The majority (76.5%) of respondersalso believes that m-learning would be useful for their students, and 86.4%of responders wereagreed toattempt to tap on the potential of using the networks and smartphones for educational purposes.The results showed positive potentials and capabilities of the smart phones use in the education. This indicates that teaching & learning could advantage from utilizing these new technological tools. Despite this positive acceptance of technology, educators‟ readiness for the use of mobile phone in teaching and learning was found to be at a considerably low level. However, the study identified a significant correlation between respondents‟ awareness and motivation towards mobile technology with their readiness for the pedagogical usage of mobile phone.